Sustainable maritime education: Integrating environmental science for global competence - Damoyanto Purba; Marudut Bernadtua Simanjuntak (University of Muhammadiyah Malang, 2024)
This research investigates the integration of Urban Environmental Quality, Materials and Resource Management, and Green and Sustainable Environment within the international maritime education framework at Sekolah Tinggi Ilmu Pelayaran (STIP Jakarta/ Maritime Institute of Jakarta). The study explores cadet experiences in Nautical, Technical, and Port and Shipping Management Majors, analysing theoretical foundations, curriculum satisfaction, practical training, and the incorporation of Environmental Science elements. Utilizing a qualitative descriptive approach, data is gathered through document analysis and self-reported reflections from 100 randomly selected cadets. The findings reveal distinct dynamics across majors, indicating a strong alignment between theoretical foundations and curriculum satisfaction. However, variations exist in the emphasis on practical training and the integration of Environmental Science elements. Port and Shipping Management Majors stand out with a notable commitment to sustainability principles, while Nautical and Technical Majors show potential areas for enhancement. The implications for future research underscore the need for ongoing refinements in curricula to address the evolving demands of the maritime industry. The study contributes to the scholarly discourse on international maritime education, providing insights for academic institutions to foster environmentally conscious and globally competent maritime professionals.